2018
DOI: 10.1186/s12966-018-0701-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of leisure-time physical activity across pregnancy and adverse pregnancy outcomes

Abstract: BackgroundAlthough leisure-time physical activity (PA) contributes to overall health, including pregnancy health, patterns across pregnancy have not been related to birth outcomes. We hypothesized that women with sustained low leisure-time PA would have excess risk of adverse pregnancy outcomes, and that changing patterns across pregnancy (high to low and low to high) may also be related to risk of adverse pregnancy outcomes.MethodsNulliparous women (n = 10,038) were enrolled at 8 centers early in pregnancy (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 35 publications
3
46
1
Order By: Relevance
“…The initiation of the PA during the first trimester is associated with lower risk for development of gestational diabetes [15][16][17][18]. Additionally, early initiation of PA during pregnancy is associated with a lower likelihood of preeclampsia [19,20] and better sleep quality [21]. This leads to further need for examination of factors that influence the PA level during the first trimester.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of the PA during the first trimester is associated with lower risk for development of gestational diabetes [15][16][17][18]. Additionally, early initiation of PA during pregnancy is associated with a lower likelihood of preeclampsia [19,20] and better sleep quality [21]. This leads to further need for examination of factors that influence the PA level during the first trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) as a modifiable health risk factor has been shown to contribute to the maternal health of women and their offspring. Several studies have reported the benefits of PA and exercise during pregnancy, which include reduced risk of excessive gestational weight gain [1][2][3][4][5], decreased risk of gestational diabetes [1,[6][7][8][9], and reduced risk of preeclampsia [10][11][12][13][14]. Evidence also indicates that PA during pregnancy lowers rates of preterm births [15,16], improves sleep [17,18], reduces the risk of caesarean section and postpartum recovery time [19][20][21], and reduces length of labour and delivery complications [22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant efforts in recent years, there remains a marked decline in PA levels during and after pregnancy [ 4 , 5 , 6 ]. Importantly, a reduction in PA has also been observed among others in the family unit, extending from pregnancy into the postpartum period [ 7 ], demonstrating the wide reaching impact on PA of this major life event.…”
Section: Physical Activity In Pregnancy and Postpartummentioning
confidence: 99%